COVID‐19 in solid organ transplant recipients: No difference in survival compared to general population. Issue 1 (2nd August 2020) - Rinaldi, Matteo; Bartoletti, Michele; Bussini, Linda; Pancaldi, Livia; Pascale, Renato; Comai, Giorgia; Morelli, Mariacristina; Ravaioli, Matteo; Cescon, Matteo; Cristini, Francesco; Viale, Pierluigi; Giannella, Maddalena
Abstract: Coronavirus disease 2019 (COVID‐19) may be associated with worse outcome in solid organ transplant (SOT) recipients. We performed a prospective cohort study of hospitalized patients with confirmed diagnosis of COVID‐19, from March 15 to April 30, 2020, at two tertiary hospitals in Emilia‐Romagna Region. SOT recipients were compared with non‐SOT patients. Primary endpoint was all‐cause 30‐day mortality. Relationship between SOT status and mortality was investigated by univariable and multivariable Cox regression analysis. Patients were assessed from COVID‐19 diagnosis to death or 30‐day whichever occurred first. Study cohort consisted of 885 patients, of them 24 SOT recipients (n = 22, kidney, n = 2 liver). SOT recipients were younger, had lower BMI, but higher Charlson Index. At admission they presented less frequently with fever and respiratory failure. No difference in 30‐day mortality between the two groups (19% vs 22.1%) was found; however, there was a trend toward higher rate of respiratory failure (50% vs 33.1%, P = .07) in SOT recipients. Superinfections were more represented in SOT recipients, (50% vs 15.5%, P < .001). At multivariate analysis adjusted for main covariates, there was no association between SOT and 30‐day mortality HR 1.15 (95% CI 0.39‐3.35) P = .79. Our data suggest that mortality among COVID‐19 SOT recipients is similar to general population.